Correlation Between Systemic Risk Factors and Diabetic Retinopathy in Patients with Diabetes Mellitus at Cicendo National Eye Hospital - Rizki Rahma Nauli; Rova Virgana; Arief Kartasasmita; Iwan Sovani; Erwin Iskandar; Grimaldi Ihsan (Indonesian Vitreoretinal Society, 2018)
Introduction: Diabetic Retinopathy (DR) is a highly specific microvascular complication of both type 1 and type 2 diabetes mellitus (DM) that can cause significant visual impairment in adult populations worldwide. The risk of having and/or developing DR is influenced by many systemic features. Identification and management of particular systemic risk factors as early as possible during the course of DM might lower incidence of further progression and severity of DR. The aim of this study is to describe the correlation between systemic risk factors and DR in patients with DM in Cicendo National Eye Hospital on December 1st 2017 – January 31st 2018. Methods: An analytical cross-sectional study. The subjects were all patients diagnosed with DR based on ophthalmology examination at outpatient clinic of Vitreoretinal Division in Cicendo National Eye Hospital. The data were analyzed using chi-square (x2) with significances of p < 0.05. Result: Seventy-one eyes were included in this study, among of which has been classified as mild NPDR (n= 1), moderate NPDR (n= 9), severe NPDR (n= 27), and PDR (n= 34). Severe NPDR group had older age distribution at range 51-60 years old (n= 18, 66.7%, p = 0.001). Stage 1 hypertension was found to be dominant in PDR group (n= 18, 66.7%, p = 0.043). Both high total serum cholesterol group (n= 27, 76.5%, p = 0.048) and high fasting blood glucose (n= 27, 79.4%, p = 0.01) were significantly present in patients with PDR. Positive (+1) urine glucose was statistically significant in PDR group. Conclusion: There were several systemic risk factors from laboratory findings correlated in patient with DR in this study, however further study is needed to determine their role for predicting progression and severity of DR.